Modulation of physiological reflexes by pain: role of the locus coeruleus - Szabadi, Elemer; Szabadi, Elemer (Frontiers in Integrative Neuroscience, 2012)
The locus coeruleus is activated by noxious stimuli, and this activation leads to inhibition of perceived pain. As two physiological reflexes, the acoustic startle reflex and the pupillary light reflex, are sensitive to noxious stimuli, this sensitivity, at least to some extent, may be mediated by the locus coeruleus. The acoustic startle reflex, contraction of a large body of skeletal muscles in response to a sudden loud acoustic stimulus, can be enhanced by both directly (“sensitization”) and indirectly (“fear conditioning”) applied noxious stimuli. The enhancement of the startle response by conditioned fear (“fear-potentiated startle”) involves the activation of the amygdala. The locus coeruleus may also be involved in both sensitization and fear potentiation: pain signals activate the locus coeruleus both directly and indirectly via the amygdala, which results in enhanced motoneurone activity, leading to an enhanced muscular response. The light reflex response is constriction of the pupil evoked by a light stimulus. The pupil is dilated by the sympathetic and constricted by the parasympathetic output to the iris. The locus coeruleus contributes to the sympathetic outflow to the iris and attenuates the parasympathetic output by inhibiting the Edinger-Westphal nucleus, the preganglionic cholinergic nucleus in the light reflex pathway. Noxious stimulation results in pupil dilation (“reflex dilation”), without any change in the light reflex response, consistent with sympathetic activation via the locus coeruleus. Conditioned fear, on the other hand, results in the attenuation of the light reflex response (“fear-inhibited light reflex”), consistent with the inhibition of the parasympathetic light reflex via the locus coeruleus. Directly applied pain and fear conditioning may affect different populations of autonomic neurones in the locus coeruleus, directly applied pain activating sympathetic and fear conditioning parasympathetic premotor neurones.